PERKEMBANGAN OOSIT INDUK Osteochilus hasselti C.V. YANG DIBERI HORMON ESTRADIOL-17β DAN PAKAN DENGAN KADAR PROTEIN BERBEDA - Andri Prajaka Santo; Untung Susilo; Gratiana E Wijayanti (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
The availability of fish seed is very important in fish propagation. Good quality of fish seeds were produced by a good brooder which characterized a large number of egg production at spawning. The aims of this research were to evaluate the oocytes development in the hard-lipped Barb (Osteochilus hasselti C.V.) given 17β-estradiol, different percentage of protein in the diet, and their combination. This research was conducted experimentally applying Factorial Completely Randomized Design. The first factor was percentage of protein in the diet consisted of 4 levels namely 25% (P1), 30% (P2), 35% (P3), and 40% (P4), the second factor was dose of 17β-estradiol benzoate (EB) consisted of 3 levels namely 0 µg/kg of body weight (D0), 126 µg/kg of body weight (D1), and 210 µg/kg of body weight (D2), thus there were 12 combinations of treatment with 3 replicates. The results showed that neither of protein proportion or 17β-estradiol affected the proportion of oocytes of any developmental stage (p>0,05) within the first two weeks post spawning. The treatments, however, significantly increased the proportion of oocytes at V3-V5, V6-V7, and post-vitellogenic stages (p<0,05) started at week 4th post spawning. The GSI increased in correlation to the proportions of oocytes at stage ≥ V6 (r=0,701; p<0,01) and the dose of 17β-estradiol (r = 0.357, p <0.05). There was no significant different on GSI amongst the experimental groups. The HSI tend to decrease as the dose of 17β-estradiol increased (r = -0.210, p> 0.05). In conclusion, the percentage of protein in the diet and different doses of 17β-estradiol improved oocyte development of Hard-Lipped Barb (Osteochilus hasselti C.V.).